Gasterosteus aculeatus hatchling length upon hatching depending on parental heatwave treatment, including average egg size of the clutch and clutch size - Helen Spence-Jones; Lisa N S Shama (PANGAEA, 2025)
Hatchling length (mm) upon hatching depending on parental heatwave treatment, and including average egg size of the clutch (mm) and clutch size (total number of eggs)
In: Spence-Jones, H; Shama, LNS (2025): Stickleback (Gasterosteus aculeatus) marine heatwave experiment: F0 adult size and fecundity traits, F1 offspring growth, behavior and survival, and F2 offspring egg size, clutch size, and hatchling length [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973487